Preparation method of SSZ-39 molecular sieve nanosheet
By controlling the water content and using SSZ-39 molecular sieve as an inducer, ultra-thin SSZ-39 molecular sieve nanosheets were prepared, which solved the problem of large crystal size and easy to twin in the prior art, significantly improved the catalytic and adsorption properties, and Improved gas separation capability.
Patent Information
- Application Number
- CN202411329028.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The crystal size of the existing SSZ-39 molecular sieve is large and uneven, and it is prone to twin growth, resulting in agglomeration to form larger particles, limiting its performance in catalysis and adsorption.
By controlling the extremely low water content in the sol, adding SSZ-39 molecular sieve as seed crystal induced synthesis, evaporation removes moisture and grinding, combined with appropriate crystallization and calcination steps, monodispersed, ultra-thin SSZ is prepared -39 Molecular Sieve Nanosheets.
The crystal thickness of SSZ-39 molecular sieve is shortened, its catalytic and adsorption properties are improved, and the adsorption selectivity to the CO2/N2 and CO2/CH4 mixed gases are enhanced. It is suitable for gas capture and catalytic reactions.
Smart Images

Figure CN119143144A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of molecular sieves, and in particular relates to a method for preparing SSZ-39 molecular sieve nanosheets. Background Art
[0002] Boiling molecular sieves are a type of inorganic microporous material with a regular pore structure, which is widely used in fields such as gas adsorption and catalysis. When molecular sieves are used as catalysts or adsorbents, their performance is usually highly correlated with parameters such as crystal size, morphology and aggregation state. The preparation of ultra-thin molecular sieve nanosheets (thickness below 100 nm) can greatly increase the specific surface area of the molecular sieve and shorten the length of the mass transfer path in the crystal, thereby improving its performance in applications such as catalysis and adsorption. SSZ-39 molecular sieve is an aluminosilicate with an AEI configuration, belonging to the orthorhombic crystal system. It is a typical octahedral small-pore molecular sieve with a three-dimensional pore structure distributed in [ 100 ]、[ 110 ]and[ 001 ] three directions, with a pore size of 3.8 Å. SSZ-39 molecular sieves have shown potential application value in gas adsorption and catalytic reactions. Zones et al. ( US-5958370 ) first reported SSZ-39 molecular sieve and its synthesis method: using cyclic quaternary ammonium salt as a structure-directing agent, USY molecular sieve was used for crystallization synthesis, and the resulting product crystal size was in the micron level. Existing literature reports mostly use the classic synthesis method disclosed by Zones et al. Sano et al. used tetraethylphosphine hydroxide (TEPOH) as a structure-directing agent to prepare SSZ-39 molecular sieve by transformation of USY molecular sieve ( Chem. Lett. 2014, 43, 302-304 ), whose crystals are cubic in shape of about 500 nm, and there is an obvious twinning phenomenon. Patent CN202211679034.9 discloses a method for preparing nano-scale SSZ-39 molecular sieves, which completes crystallization at a stirring speed of 50-300 rpm, and the size of the synthesized SSZ-39 molecular sieve is 100-600 nm. Xu et al. ( Microporous and Mesoporous Materials 312 (2021) 110736 ) USY molecular sieve was used to synthesize SSZ-39 molecular sieve by crystallization, and a flat SSZ-39 molecular sieve with a thickness of 200 nm was obtained. Xiao Fengshou et al. reported the successful synthesis of SSZ-39 molecular sieve using silica sol as the silicon source ( ACS Appl. Mater. Interfaces 2019, 11, 23112-23117 ), however, the crystals grew in agglomerates and the yield was very low.
[0003] The synthesis of existing SSZ-39 molecular sieves has the following two problems: First, the size of SSZ-39 crystals is large and uneven, and the size in its three-dimensional direction is still above 200 nm; second, SSZ-39 crystals are very easy to grow by twinning, resulting in agglomeration to form larger particles. As a result, the micropores of existing SSZ-39 molecular sieves are relatively long, which limits the mass transfer and diffusion of guest molecules, resulting in low efficiency of SSZ-39 molecular sieves when used as catalysts, and easy carbon deposition. When used for adsorption separation, the adsorption rate is slow and the adsorption effect is not ideal. Summary of the invention
[0004] In view of the shortcomings of the prior art in synthesizing SSZ-39 molecular sieves, the object of the present invention is to provide a method for preparing monodisperse, ultrathin SSZ-39 molecular sieve nanosheet crystals. The key to realizing the synthesis of ultrathin SSZ-39 molecular sieves in the present invention is to remove the water in the reaction system by means of evaporation, etc., control the extremely low water content in the sol, and add SSZ-39 molecular sieves as seeds to induce synthesis. The preparation method provided by the present invention is simple, and can obtain ultrathin SSZ-39 molecular sieve nanosheets with good monodispersity and no twins, the thickness of which can be controlled at 30 nm, which can greatly shorten the mass transfer channel inside the crystal, and effectively improve the catalytic performance and adsorption performance of SSZ-39 molecular sieves.
[0005] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions: A method for preparing SSZ-39 molecular sieve nanosheets, the preparation process comprising the following steps: (1) Mix silicon source, aluminum source, USY molecular sieve, template (SDA), sodium hydroxide, and water and stir evenly, continue stirring and aging for 1 to 72 hours to obtain a gel, the molar ratio of the active ingredients of which is: SiO2 / Al2O3=5~200, Na2O / SiO2=0.05~0.5, SDA / SiO2=0.1~1.0, H2O / SiO2=4~100.
[0006] (2) Add SSZ-39 molecular sieve seed crystals to the gel in step (1), stir evenly, evaporate the water in the gel at 40-90°C until the H2O / SiO2 ratio reaches a certain value, and then grind it to obtain a dry gel.
[0007] (3) The dry gel of step (2) is placed in a reactor and crystallized at 130-220°C for 1-9 days. The reaction product is collected by centrifugation and washed to neutrality, and then dried at 40-80°C. Finally, the template is removed by calcination at 450-650°C for 4-10 hours to obtain SSZ-39 molecular sieve nanosheets.
[0008] Preferably, the silicon source includes one or more of sodium silicate, silicon powder, silica sol, solid silica gel or tetraethyl orthosilicate.
[0009] Preferably, in step (1), the aluminum source includes one or more of sodium aluminate, aluminum hydroxide, metallic aluminum, pseudo-boehmite or aluminate.
[0010] Preferably, in step (1), the SiO2 / Al2O3 molar ratio of the USY molecular sieve is 5-120.
[0011] Preferably, in step (1), the SDA is hydroxide N,N -Dimethyl-3,5-dimethylpiperidinium, hydroxide N, N - one or more of diethyl-2,6-dimethylpiperidinium, tetraethylphosphine hydroxide, tetrapropylphosphine hydroxide, tetrabutylphosphine hydroxide or tetraethylammonium hydroxide.
[0012] Preferably, in step (1), the effective ingredient SiO2 in the gel is provided by USY molecular sieve and silicon source, and the molar ratio of the two, SiO2 (silicon source) / SiO2 (USY), is 0-9 based on SiO2.
[0013] Preferably, in step (2), the molecular sieve seed is SSZ-39 molecular sieve. The molar ratio of the prepared gel is: SiO2 / Al2O3=10~200, Na2O / SiO2=0.05~0.5, SDA / SiO2=0.01~1.0, H2O / SiO2=10~200. The gel is crystallized at 130~220°C for 1~4 days, the product is collected by centrifugation and washed to neutrality, then dried at 40~80°C, and calcined at 550°C for 10 hours to remove the template.
[0014] Preferably, in step (2), the mass of the added SSZ-39 molecular sieve seed crystals is 0.5-20 wt % of the total mass of SiO2 in the gel of step (1).
[0015] Preferably, in step (2), the dry gel has a molar ratio of H2O / SiO2=0.1~4.
[0016] The present invention provides the monodisperse SSZ-39 molecular sieve nanosheet prepared by the preparation method described in the above technical solution, and the crystal thickness is less than 200 nm. Preferably, the SSZ-39 molecular sieve nanosheet crystal thickness is 100 nm, and more preferably, the SSZ-39 molecular sieve nanosheet crystal thickness is 30 nm.
[0017] Another aspect of the present invention provides an adsorption separation application of the monodisperse SSZ-39 molecular sieve nanosheets. The SSZ-39 molecular sieve nanosheets are used as CO2 adsorption materials and can be used to separate mixtures such as CO2 / N2 and CO2 / CH4.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention controls the extremely low water content in the synthetic gel and uses the SSZ-39 molecular sieve as a seed crystal to synthesize a monodisperse SSZ-39 molecular sieve with a nanosheet morphology, wherein the crystal thickness is less than 100 nm, preferably 30 nm. The SSZ-39 molecular sieve nanosheets synthesized by the present invention have uniform size, good monodispersity, and no crystal aggregation. The specific surface area of the SSZ-39 molecular sieve nanosheets synthesized by the present invention is as high as 773 m 2 / g, and its ideal adsorption solution theory (IAST) selectivity for 15 / 85 (v / v) CO2 / N2 and 15 / 85 (v / v) CO2 / CH4 mixed gases is greater than 1000 and 130 respectively. It is suitable for capturing CO2 in gases such as natural gas and flue gas, and can also be used as a catalyst material for catalytic reactions such as SCR and MTO. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD patterns of the SSZ-39 molecular sieve nanosheets synthesized in Examples 1 to 6 and Comparative Example 1 are shown.
[0020] Figure 2 The scanning electron microscope images of the SSZ-39 molecular sieve nanosheets synthesized in Examples 1 to 3 and Comparative Examples 1 to 2 are shown.
[0021] Figure 3 This is a transmission electron micrograph of the SSZ-39 molecular sieve nanosheets synthesized in Example 1.
[0022] Figure 4 This is the CO2, N2, and CH4 adsorption isotherms of the SSZ-39 molecular sieve nanosheets synthesized in Example 1.
[0023] Figure 5 This is the CO2 / N2 penetration curve of the SSZ-39 molecular sieve nanosheets synthesized in Example 1.
[0024] Figure 6 This is the CO2 / CH4 penetration curve of the SSZ-39 molecular sieve nanosheets synthesized in Example 1. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention. The specific implementation is only used to explain the present invention and does not affect the protection scope of the present invention. Example 1
[0026] (1) 2.08 g silica sol (40 wt%), 0.14 g aluminum hydroxide, 0.92 g USY molecular sieve (SiO2 / Al2O3 molar ratio of 15), 0.18 g NaOH, 2.6 g hydroxide N,N- Dimethyl- 3,5 -Dimethylpiperidine solution (25%) and 3.0 g of deionized water were mixed and stirred for 1 hour to obtain a gel, the molar ratio of its active ingredients was: SiO2 / Al2O3=15, Na2O / SiO2=0.08, SDA / SiO2=0.5, H2O / SiO2=10, among which the ratio of SiO2 (silicon source) / SiO2 (USY) was 1.
[0027] (2) 6.9 g silica sol, 0.05 g aluminum hydroxide, 1.0 g USY molecular sieve, 1.02 g NaOH, 6.9 g hydroxide N,N- Dimethyl- 3,5 -Dimethylpiperidine solution (25%) and 4.4 g of deionized water were mixed and stirred for 3 hours to obtain a seed synthesis sol, which was transferred to a reactor and heated at 160 The reaction was carried out at ℃ for 3 days, the product was collected by centrifugation and washed to neutrality, then dried at 80℃, and calcined at 550℃ for 10 hours to remove the template, thereby obtaining SSZ-39 molecular sieve seed crystals.
[0028] (3) Add 0.07 g of SSZ-39 seed crystals prepared in step (2) (2% of the mass of SiO2 in the gel) to the gel of step (1), stir evenly, place on a 90°C heater, heat to evaporate the water, calculate the H2O / SiO2 ratio by weighing its mass change, and when the molar ratio of H2O / SiO2 is 0.1, grind the gel thoroughly to form a dry powder xerogel.
[0029] (4) The dry gel from step (3) was transferred to a reactor and crystallized at 140 °C for 7 days. After the reaction was completed, the product was collected by centrifugation, washed with deionized water until neutral, and then dried in a 60 °C oven. The dried product was calcined at 450 °C for 10 h to obtain activated SSZ-39 molecular sieve nanosheets, which were labeled as NS-1.
[0030] The XRD pattern of NS-1 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve, the SEM image of NS-1 is shown in Figure 2 a, showing nanosheet-like morphology, uniform size, crystal length and width of 300 nm, thickness of 30 nm. TEM image of NS-1 is shown in Figure 3 , showing that its largest crystal surface is (001)Crystal surface; its gas adsorption isotherm is as follows Figure 4 As shown in Figure 2, at 100 kPa, the ratios of CO2 / N2 and CO2 / CH4 adsorption are 11 and 5, respectively, and their specific surface area and micropore volume are 773 m 2 / g and 0.31 m 3 / g. To further demonstrate the CO2 separation performance of the synthesized SSZ-39 molecular sieve nanosheets, the penetration curves of 15 / 85 v / v CO2 / N2 and CO2 / CH4 mixed gases were tested at room temperature. Figures 5 and 6 As shown. It shows that SSZ-39 molecular sieve nanosheets NS-1 have excellent CO2 / N2 and CO2 / CH4 separation performance and can be used for gas adsorption separation. Example 2
[0031] The synthesis steps of SSZ-39 molecular sieve are the same as those in Example 1, except that the SiO2 / Al2O3 molar ratio of USY molecular sieve in step (1) is 120, and the silicon source is tetraethoxysilane; the molar ratio of the effective ingredients in the gel is SiO2 / Al2O3=200, Na2O / SiO2=0.2, SDA / SiO2=0.1, and H2O / SiO2=100; in step (3), the mass of SSZ-39 seed crystals added is 20 wt% of the total mass of gel SiO2, and the gel is evaporated until the molar ratio of H2O / SiO2 is 4; in step (4), the reaction temperature is 130°C and the crystallization time is 9 days. The synthesized product is calcined at 650°C for 4 h and is marked as NS-2.
[0032] The XRD pattern of NS-2 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve, the SEM image of NS-2 is shown in Figure 2 b, showing that its size is uniform, with the length and width of the crystal being 700 nm and the thickness being 100 nm. Example 3
[0033] The synthesis steps of SSZ-39 molecular sieve are the same as those in Example 1, except that the template in step (1) is hydroxide N,N-diethyl-2,6-dimethylpiperidinium solution (55%), the aluminum source is sodium aluminate, the molar ratio of SiO2 / Al2O3 of USY molecular sieve is 5, the gel is aged for 72 hours, and the molar ratio of the effective ingredients in the gel is SiO2 / Al2O3=30, Na2O / SiO2=0.05, SDA / SiO2=1.0, H2O / SiO2=10; in step (3), the mass of SSZ-39 seed crystals added is 0.5 wt% of the total mass of gel SiO2, and the water is evaporated at 40 ° C until the molar ratio of H2O / SiO2 of the dry gel is 1.4; in step (4), the reaction temperature is 160 ° C and the crystallization time is 5 days. The synthesized product is calcined at 550 ° C for 6 h and is marked as NS-3.
[0034] The XRD pattern of NS-3 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve, the SEM image of NS-2 is shown in Figure 2 c, showing that its size is uniform, with the length and width of the crystal being 600 nm and the thickness being 70 nm. Example 4
[0035] The synthesis steps of SSZ-39 nanosheets are the same as those in Example 1, except that no other silicon source and aluminum source are added when preparing the gel in step (1), and only USY molecular sieve is added to provide silicon source and aluminum source, and the molar ratio of SiO2 (silicon source) / SiO2 (USY) is 0. The product is placed in an oven at 60°C to dry, and the dried product is calcined at 650°C for 4 h. The product is marked as NS-4.
[0036] The XRD pattern of NS-4 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve. Its size is uniform, the length and width of the crystal are 400 nm, and the thickness is 30 nm. Example 5
[0037] The synthesis steps of SSZ-39 nanosheets are the same as those in Example 1, except that in step (1), the template is hydroxide N,N -diethyl-2,6-dimethylpiperidinium, the molar ratio of the active ingredients in the gel is SiO2 / Al2O3=5, Na2O / SiO2=0.5, SDA / SiO2=0.08, H2O / SiO2=4, and the molar ratio of SiO2 (silicon source) / SiO2 (USY) is 9; in step (4), the crystallization temperature is 220°C and the synthesis time is 1 day. The product is marked as NS-5.
[0038] The XRD pattern of NS-5 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve. Its size is uniform, the length and width of the crystal are 300 nm, and the thickness is 30 nm. Example 6
[0039] The synthesis steps of SSZ-39 nanosheets are the same as those in Example 1, except that the molar ratio of H2O / SiO2 in the dry gel in step (3) is 0.5; the crystallization synthesis temperature of the dry gel in step (4) is 180°C, and the reaction time is 3 days. The product is labeled NS-6.
[0040] The XRD pattern of NS-6 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve. Its size is uniform, the length and width of the crystal are 400 nm, and the thickness is 50 nm. Comparative Example 1
[0041] The synthesis steps of SSZ-39 molecular sieve are the same as those in Example 1, except that no SSZ-39 molecular sieve seed crystals are added in step (3); in step (4), the reaction temperature is 140°C and the crystallization time is 9 days. The synthesized product is marked as NS-7.
[0042] The XRD pattern of NS-7 is shown in Figure 1 , indicating that it is pure SSZ-39 molecular sieve. Its SEM picture is as follows Figure 2 As shown in d, the product size is uneven, the length and width of the crystal are 1~2 μm, and the thickness is 300 nm ( Figure 2 d). Comparative Example 2
[0043] The synthesis steps of SSZ-39 molecular sieve are the same as those in Example 1, except that in step (3), the molar ratio of H2O / SiO2 in the gel is 5.0. The synthesized product is labeled NS-8.
[0044] The SEM image of NS-8 is shown in Figure 2 e. It is observed in the figure that the product contains impurities, and the crystal size of SSZ-39 molecular sieve is about 5μm, and the crystal thickness is greater than 500 nm.
Claims
1. A method for preparing SSZ-39 molecular sieve nanosheets, characterized in that: The preparation process includes the following steps: (1) Mix silicon source, aluminum source, USY molecular sieve, template (SDA), sodium hydroxide, and water and stir evenly, continue stirring and aging for 1 to 72 hours to obtain a gel, the molar ratio of the active ingredients of which is: SiO2 / Al2O3=5~200, Na2O / SiO2=0.05~0.5, SDA / SiO2=0.1~1.0, H2O / SiO2=4~100; (2) adding SSZ-39 molecular sieve seed crystals to the gel in step (1), stirring evenly, evaporating the water in the gel at 40-90°C until the H2O / SiO2 ratio reaches a certain value, and then grinding the gel to obtain a dry gel; (3) The dry gel of step (2) is placed in a reactor and crystallized at 130-220°C for 1-9 days. The reaction product is collected by centrifugation and washed to neutrality, and then dried at 40-80°C. Finally, the template is removed by calcination at 450-650°C for 4-10 hours to obtain SSZ-39 molecular sieve nanosheets.
2. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (1), the silicon source includes one or more of sodium silicate, silicon powder, silica sol, solid silica gel or tetraethyl orthosilicate.
3. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (1), the aluminum source includes one or more of sodium aluminate, aluminum hydroxide, metallic aluminum, pseudo-boehmite or aluminate.
4. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (1), the SiO2 / Al2O3 molar ratio of the USY molecular sieve is 5-120.
5. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (1), the SDA is a hydroxide N,N -Dimethyl-3,5-dimethylpiperidinium, hydroxide N,N - one or more of diethyl-2,6-dimethylpiperidinium, tetraethylphosphine hydroxide, tetrapropylphosphine hydroxide, tetrabutylphosphine hydroxide or tetraethylammonium hydroxide.
6. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (1), the effective ingredient SiO2 in the gel is provided by USY molecular sieve and silicon source, and the molar ratio of the two, calculated as SiO2, SiO2 (silicon source) / SiO2 (USY), is 0-9.
7. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (2), the molecular sieve seed is SSZ-39 molecular sieve. The molar ratio of the prepared gel is: SiO2 / Al2O3=10~200, Na2O / SiO2=0.05~0.5, SDA / SiO2=0.01~1.0, H2O / SiO2=10~200. The gel is crystallized at 130~220°C for 1~4 days, the product is collected by centrifugation and washed to neutrality, then dried at 40~80°C, and calcined at 550°C for 10 hours to remove the template.
8. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (2), the mass of the added SSZ-39 molecular sieve seed crystals is 0.5-20 wt% of the total mass of SiO2 in the gel of step (1).
9. The method for preparing SSZ-39 molecular sieve nanosheets according to claim 1, characterized in that: In step (2), the dry gel has a molar ratio of H2O / SiO2=0.1~4.
Citation Information
Patent Citations
Preparation method and application of nanoscale SSZ-39 molecular sieve
CN116199236A
Cited By
Synthesis method of two-dimensional nanosheet SSZ-39 molecular sieve
CN121948482A
